Chemicao composition of the leaf oil of Litsea glutinosa (Lour.) C. B. Rob. from Ha Tinh provinve - Hien, Nguyen Thu; Thang, Tran Dinh; Dai, Do Ngoc; Thai, Tran Huy (VNU Journal of Science: Natural Sciences and Technology; Vol 26 No 3, 2010)
Abstract